EFEKTIVITAS PELAKSANAAN PENERTIBAN TRUK BERTONASE BERAT DI KOTA PEKANBARU - Yola Yuanggraini. R; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
In this case the researchers behind on the phenomenon of the number of heavy tonnage trucks passing in Pekanbaru city on a busy schedule of vehicles and the number of trucks that are just passing not passing through a predefined path . The purpose of this study was to determine how the effectiveness of the implementation of the control of heavy tonnage trucks in Pekanbaru and the factors that influence the implementation of the demolition truck tonnage in Pekanbaru with the aim of creating security , comfort in traffic .The theory used in this research is the theory according to Gibson on measuring the effectiveness of an activity. Informants in this study is the Department of Transportation, Communication and Information Unit Pekanbaru and Pekanbaru Traffic Police. The method used in this research is descriptive qualitative data collection techniques through observation, interview and literature study.The results showed that the effectiveness of the implementation of the demolition of heavy tonnage trucks in Pekanbaru has not done well. In other words, there are still many problems that arise in its implementation. Such as lack of equipment, careful planning, special programs and surveillance systems. This causes the control does not run as expected. The factors that affect the implementation of the control of heavy tonnage trucks, among others, the lack of human resources, funds, and awareness of the driver. It has a very important influence on the effectiveness of policing heavy tonnage trucks in Pekanbaru.Keywords: Effectiveness, Implementation, Control.